PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN MOBIL SEBAGAI KENDARAAN PRIBADI - Martujan Martujan; Tukirin Tukirin (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2022)
The purpose of study was to determine the effect of product quality and price on the decision to purchase a private car. Study used a survey method with judgment sampling technique, and the number of samples that met the criteria were 100 respondents, and there were 92 respondents who filled the questionnaire. Data collection techniques were questionnaires and measurements using the Linkert scale. The data processing and analysis techniques were descriptive statistical analysis, and multiple linear correlation regression analysis. The results showed that the average product quality score (X1) was 4.04 and Â price (X2) was 3.89, then purchase decision (Y) was 4.04. The results of multiple linear regression analysis obtained multiple linear regression equation = 3.644 + 0.240X1 + 0.403X2 . From the classical assumption test, no violations were found, so the regression is Best Linear Unbiased Estimator (BLUE). The results of analysis of determination (R2) obtained the Adjusted R square value of 0.482. Based on the results of the partial hypothesis test (t test) the product quality variable (X1) is 0.000 <0.05, so partially it has a significant effect on the decision to buy a private car. The significance value for price variable (X2) is 0.000 <0.05, so partially it has a significant effect on the decision to buy a private car. The results of simultaneous hypothesis testing (F) obtained a significance value of 0.000 <0.05, so product quality and price simultaneously have a significant effect on purchasing decisions for private cars.Â Keywords: Product Quality; Price; Buying decision